Optimizing nutrition and metabolism in a severely burned patient during prolonged continuous renal replacement therapy: a case report - Shan, Haili; Cheng, Xiang; Hong, Yulu; Shen, Tao; You, Chuangang; Han, Chunmao (Frontiers in Nutrition, 2026)
It is rare for patients to survive and be discharged with extensive severe burns in combination with severe acute kidney injury (AKI). The case under discussion involved a patient who had sustained critical burn injuries, with 96% of the patient’s total body surface area affected, 80% of which were categorized as third-degree burns. Severe AKI was observed on the initial day following the burn injury, and continuous renal replacement therapy (CRRT) was commenced on the subsequent day. In response to inadequate oral intake, long-term enteral and supplemental parenteral nutrition was administered. To address the hypermetabolic state and promote wound healing, a dynamic, individualized nutritional support plan was implemented during the patient’s hospitalization. Regular monitoring of patients’ resting energy expenditure via indirect calorimetry ensures adequate energy and nutrient substrates are provided, while administering growth hormone to promote wound healing. Nutritional therapy efficacy is dynamically assessed through wound healing rate, clinical signs, serum prealbumin levels, and other relevant indicators to guide timely adjustments in nutritional intervention. On the 96th day, the patient’s wound had mostly healed and was transferred to a rehabilitation facility for continued treatment. This case presents an exceptionally complex clinical scenario, combining extensive burns with acute kidney injury. During a period of 95 consecutive days of CRRT, the burn wounds achieved substantial healing and the patient survived to discharge. A comparison with previously published case reports indicates that the case we report is distinguished by a larger total burn surface area, a prolonged course of CRRT, and a markedly more convoluted clinical trajectory. A precise, continuously refined nutritional support strategy and multidisciplinary team collaboration were instrumental in achieving a favorable outcome.